Linking wellbeing to success: life satisfaction on mathematics performance of Philippine public high school students - Estipona, Elisa P.; Delos Santos, Maria Salud M. (Frontiers in Education, 2025)
This study examined the influence of Grade 11 students’ life satisfaction domains—family, friends, neighborhood, school, and self—on their academic performance in mathematics in a secondary public school in Cebu City, Philippines. A quantitative descriptive-correlational research design was employed, with data collected from 184 respondents out of a population of 340 Grade 11 students. A 30-item questionnaire adapted from Schnettler et al. (2017) measured life satisfaction levels, while academic performance in mathematics was categorized based on school grading standards. Results indicated that students reported high satisfaction in the family and friends domains, while the neighborhood domain had comparatively lower satisfaction. Most students’ mathematical performance fell within the Satisfactory and Fairly Satisfactory categories. Statistical analysis revealed no significant correlation between life satisfaction in the domains of family, friends, school, and self with mathematical performance; however, a statistically significant relationship was observed between neighborhood satisfaction and academic achievement in mathematics, suggesting that the immediate residential environment may modestly influence student performance. These findings highlight the role of external environmental factors in academic success, emphasizing the need for a supportive neighborhood setting. Based on the results, an enhancement plan was developed and recommended for implementation to help improve students’ mathematical performance.